Efectuati: a) (2+√5)²=
B) (√5+√6)²=
c) (√6-√2)²=
d) (5-√3)²=
e) (√5-√3)(√5+√3)=
f) (√6-2)(√6+2)=
Răspunsuri la întrebare
Răspuns de
15
a). (2+√5)² = 4+4√5+5=9+4√5
b). (√5+√6)² = 5+6+2*√(5*6)=11+2√30
c). (√6-√2)² = 6+2-2√12 = 8 - 2√(4*3) = 8 - 4√3
d). ... = 25+3-10√3 = 28 - 10√3
e). ... = √5 ² - √3 ² = 5 - 3 = 2
f). ... = √6 ² - 2 ² = 6 - 4 = 2
b). (√5+√6)² = 5+6+2*√(5*6)=11+2√30
c). (√6-√2)² = 6+2-2√12 = 8 - 2√(4*3) = 8 - 4√3
d). ... = 25+3-10√3 = 28 - 10√3
e). ... = √5 ² - √3 ² = 5 - 3 = 2
f). ... = √6 ² - 2 ² = 6 - 4 = 2
Alte întrebări interesante
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă